A ways and means analysis of sub-state political violence - Blocksome, Patricia J. (Kansas State University, 2017)
This project examines the choices that rebel groups make between different types of sub-state political violence campaigns. I argue that rebels will choose a specific campaign type based on variations in the levels of state actions that cause grievances (referred to as coercion), and the capacity of both the state and the rebel group. This project develops a framework to explain the rebel decision-making process. The rebels seek to change the political behavior of the state by undertaking some form of violent campaign. Rebel campaigns are the ways in which rebels seek to obtain their ends; this project delineates between terrorist, insurgent, and civil war campaigns. However, rebels’ choice of campaign is affected by several factors: coercion, state administrative capacity, state military capacity, rebel administrative capacity, and rebel military capacity. I hypothesize that the different types of campaigns are affected differently by these factors. Additionally, I hypothesize that levels of coercion are more strongly related to the initial year of the campaign than subsequent years, regardless of campaign type. These hypotheses are analyzed via quantitative and qualitative methods. Quantitatively, this includes the development of novel latent variables for coercion and capacity prior to empirical testing of the hypotheses. Qualitatively, two case studies of rebel groups are examined; the Mau Mau in Kenya and the LTTE in Sri Lanka. The research finds limited support for the hypotheses regarding the relationships between coercion and capacity, and the rebels’ choice of campaign.
Keywords: Rebel groups; Rebel campaigns; Coercion; Capacity